Gobierno electrónico, incidencia de la incorporación de servicios electrónicos en el índice de satisfacción del usuario. caso de análisis: Registro Civil de Ecuador - Bautista Buitrón, Carlos Fernando (2018)
The purpose of this article is to describe the incidence that exists of the variable that measures the perception of quality that citizens have of the service they are receiving in the Agencies of the General Directorate of Civil Registry, Identification and Certification of the Republic of Ecuador (DIGERCIC), on the variable that represents the production indices of the services requested. The data analyzed include the period March 2016 to October 2017.